Prognostic markers of meningococcal disease in children: recent advances and future challenges. Issue 11 (November 2014) - Montero-Martín, María; Inwald, David P; Carrol, Enitan D; Martinón-Torres, Federico
<x xml:space="preserve">Abstract</x> Meningococcal disease is a life-threatening condition and a major cause of bacterial meningitis and sepsis worldwide. In many fatal cases, meningococcal disease is rapidly progressive and death occurs within hours of the initial symptoms. The early identification of patients at high risk of death would be useful in order to provide aggressive and more personalized clinical management with the proper level of supportive therapy required, contributing to an improvement in the survival rate and reduction in sequelae. The current study aims to review the current published literature about prognostic markers of meningococcal sepsis in children in order to elaborate conclusions and recommendations that could guide clinical practice and further research.